Estimating the wind energy potential over the coastal stations of Nigeria using power law and diabatic methods - Oluleye A.; Ogungbenro S. B. (African Journal of Environmental Economics and Management, 2019)
The suitability of two coastal stations in Nigeria for wind energy generation is presented in this study. To estimate the wind speeds at the desired height 70 m for standard wind turbine, two methods; namely power law relationship and diabatic evaluation have been considered. It was found that the diabatic evaluation method performed better because certain physical conditions of farm site are included in the method. Thus when potential site data are not available diabatic method can provide a good approximation of wind speeds. Comparing the energy potential of the two coastal stations, Lagos and Calabar in this study, it was found that Lagos has stronger wind speeds than Calabar especially during peak periods. The atmospheric condition most suitable to obtain maximum wind speeds was also found to be during stable condition. Stable condition occurs mostly in the night time.